PENGARUH KETIMPANGAN PENDAPATAN, PERSEPSI KORUPSI, KESETARAAN GENDER, DAN TEKNOLOGI TERHADAP KEBAHAGIAN DI NEGARA-NEGARA G20 - Annisa Oktafira; Erni Panca Kurniasih; Yanto Yanto; Sri Kurniawati; Nurul Bariyah (Universitas Pendidikan Ganesha, 2025)
Every country aims to increase the level of happiness in the community by building economic cooperation to strengthen the economy and minimize the occurrence of excessive global crises. One of the collaborations formed is the Group of Twenty (G-20). Countries that are members of the G20 represent the political and economic might of the world, and their members account for more than half of the world's population. Despite being a sizable contributor to the global economy, low happiness levels are still a problem experienced by some G20 member countries. This research evaluates and assesses the impact of income inequality, perceived corruption, gender equality, and technology on happiness in G20 countries. Panel data is secondary data from 18 G20 member countries from 2018 to 2022. This research method uses multiple linear regression processed with Eviews 10. The results show that the perception of corruption partially has a positive and significant effect. At the same time, there is no significant effect of income inequality, gender equality, and technology on happiness in G20 countries. Based on the results of this study, the government is expected to be firmly committed to eradicating corruption, which can improve people's perceptions of corruption. Furthermore, the government also needs to reduce the gap or inequality to achieve happiness and welfare inclusively for all levels of society, not only in terms of the economy. The government must also pay attention to gender equality and innovate in technology.